Peer to Peer Lending Business Agility Strategy for Fintech Startups in the Digital Finance Era in Indonesia - Hussain, Nazim (Pandawan Sejahtera Indonesia, 2023)
Technology advancements have boosted financial technology literacy, and Fintech businesses have entered the peer-to-peer lending market to fill the gap between traditional banking and people who cannot obtain financing from banks. Financial facilitation can now be done in a more streamlined, quick, and economical manner thanks to technology. With the legislation of Authority of Financial Services Number 77/POJK.01/2016 Indonesian Fintech about information technology-based money lending services, the government has safeguarded consumers in Indonesia, where fintech has significant potential. The goal of this study is to provide an example of a business agility strategy used by financial technology firms that engage in peer-to-peer lending. This study used a qualitative research strategy combined with a descriptive methodology. Literature study is the method of data collection used. The findings demonstrate that P2P lending organizations have already employed a strategy of business agility to win clients in Indonesia's digital financial era by utilizing platform technology they have created, which is a straightforward tool for achieving competitive advantages.